Matemática financeira no ensino médio : capitalização e amortização com o uso de planilha eletrônica - MARQUES, Ernande (2016)
The Financial Mathematics has a role of great importance for high school students, it is in this stage of life that many of these students enter the labor market and start using cash more often. However, it is clear that more contextualized intervention is necessary on this topic so that these students can take ownership of them. Given the above, the proposed contents in this research include the study of amount, interest, fees, inancing, loans and applications so that students can become familiar with these issues of financial mathematics and use them when needed, in their day to day. In order to enhance scientific knowledge and to provide basis to students in their academic careers, does not open up hand to show and use the formulas and relevant equations Financial Mathematics, becoming the LibrOffice Calc spreadsheet just a tool or means that facilitates, but does not replace the mathematical deductions. Therefore, the aim is always the development of skills relacionas reflection and criticism, in the examples of each topic, so that students are able to make informed decisions and responsible to situations which are required the use of Financial Mathematics.